Characterization of three rapidly growing novel Mycobacterium species with significant polycyclic aromatic hydrocarbon bioremediation potential - Deng, Yang; Mou, Tong; Wang, Junhuan; Su, Jing; Yan, Yanchun; Zhang, Yu-Qin (Frontiers in Microbiology, 2023)
Mycobacterium species exhibit high bioremediation potential for the degradation of polycyclic aromatic hydrocarbons (PAHs) that are significant environmental pollutants. In this study, three Gram-positive, rapidly growing strains (YC-RL4T, MB418T, and HX176T) were isolated from petroleum-contaminated soils and were classified as Mycobacterium within the family Mycobacteriaceae. Genomic average nucleotide identity (ANI; < 95%) and digital DNA–DNA hybridization (dDDH; < 70%) values relative to other Mycobacterium spp. indicated that the strains represented novel species. The morphological, physiological, and chemotaxonomic characteristics of the isolates also supported their affiliation with Mycobacterium and their delineation as novel species. The strains were identified as Mycobacterium adipatum sp. nov. (type strain YC-RL4T = CPCC 205684T= CGMCC 1.62027T), Mycobacterium deserti sp. nov. (type strain MB418T = CPCC 205710T=KCTC 49782T), and Mycobacterium hippophais sp. nov. (type strain HX176T= CPCC 205372T= KCTC 49413T). Genes encoding enzymes involved in PAH degradation and metal resistance were present in the genomes of all three strains. Specifically, genes encoding alpha subunits of aromatic ring-hydroxylating dioxygenases were encoded by the genomes. The genes were also identified as core genes in a pangenomic analysis of the three strains along with 70 phylogenetically related mycobacterial strains that were previously classified as Mycolicibacterium. Notably, strain YC-RL4T could not only utilize phthalates as their sole carbon source for growth, but also convert di-(2-ethylhexyl) phthalate into phthalic acid. These results indicated that strains YC-RL4T, MB418T, and HX176T were important resources with significant bioremediation potential in soils contaminated by PAHs and heavy metals.